Sistem Irigasi Pada Sawah Bertingkat Menggunakan Wireless Sensor Network - Amrin Rosada; Mochammad Hannats Hanafi Ichsan; Gembong Edhi Setyawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Agriculture is a livelihood for the people of Indonesia. Agriculture in Indonesia is carried out in a traditional system and carried out on makeshift land. The problem that is often experienced by farmers is the problem of irrigation such as being unable to check and control irrigation systems and one of the most important factors in increasing agricultural production. Irrigation is the activity of giving water to agricultural land with the aim of making the soil wetter so that the roots of plants grow well. To help farmers in conducting irrigation, WSN technology is needed to control and check irrigation systems. In this modern era the application of netwrok wireless sensors has greatly increased, given its ability to distribute and disseminate data wirelessly. In this study will make an irrigation system using a wireless sensor network to facilitate farmers in conducting irrigation. By using Arduino Uno as a microcontroller to process data, ultrasonic sensors for reading distance or high, servo as open doorstop, NRF24L01 as communication between nodes and bluetooth is used for communication with Android. The test results that have been carried out by this system can run as desired where each node can communicate with each other, servo works well can open and close water channels and ultrasonic sensors are able to detect water levels. From the results of the experiment processing time of 15 times land 1 to land 3 or land 3 and land 1 is 524.66 ms and from land 2 to land 3 or land 3 to land 2 is 405.33 ms.